The Effect of Discipline and Work Environment on Employee Productivity of Palm Oil Factory (PKS) of PT. Perkebunan Nusantara V Sei. Rokan, Pagaran Tapah Subdistrict, Rokan Hulu Regency, Riau - Putriana; Chalif Ahmad Sahputra (Asosiasi Dosen Akuntansi Indonesia, 2021)
There are problems that affect the work productivity of the employees of PT Perkebunan Nusantara V Sei Rokan, Pagaran Subdistrict, Tapah, Rokan Hulu Regency, Riau. Thus, this study aims to analyze the effect of discipline and work environment on employee productivity. The quantitative method with the SPSS analysis tool was employed in this study. 111 employees of the Palm Oil Mill (Pabrik Kelapa Sawit, abbreviated as PKS) of PT Perkebunan Nusantara V Sei Rokan, Pagaran Subdistrict, Tapah, Rokan Hulu Regency, Riau, selected using random sampling procedures, were involved in this study. The results showed that there was an effect of work discipline on employee work productivity; there was no influence of the work environment on employee work productivity; simultaneously, discipline and work environment had an effect on employee work productivity. 65.1% of work productivity can be explained by discipline and work environment while the rest was influenced by other factors. The company should pay attention to and improve things related to the work environment that might make employees feel comfortable and calm at work to increase employee work productivity.